Effects of Caffeine on THP-1 Myelogenous Cell Inflammatory Gene Expression - Zeyar T. Htun; Thomas M. Raffay; Richard J. Martin; Peter M. MacFarlane; Tracey L. Bonfield (Current Issues in Molecular Biology)
Caffeine is administered to preterm infants in neonatal intensive care units for prevention and treatment of apnea of prematurity. Although caffeine’s primary effect is to impact the respiratory drive of preterm infants, caffeine also has anti-inflammatory properties. This study investigated the role of caffeine on the inflammatory gene expression in THP-1 pre-monocytes exposed to lipopolysaccharide (LPS) in vitro, mimicking a clinical pro-inflammatory scenario. The effects of different physiologic dosages of caffeine administration post-LPS (treatment with caffeine) and pre-LPS (prophylaxis with caffeine) on pro-inflammatory gene expressions (TNF-α, NF-κB, IL-8, PPARγ) of the THP-1 cells were investigated. The post-LPS group showed a dose-dependent decrease in TNF-α at a caffeine concentration of 100 μM and NF-κB gene expression at 50 and 100 μM, with the implication that this is an optimal anti-inflammatory caffeine concentration range. Clinically, this would correspond to a serum caffeine level between 10 and 20 μg/mL, respectively. For the pre-LPS group, TNF-α and NF-κB gene expression decreased at all studied caffeine concentrations. These findings point to caffeine’s potential therapeutic capacity in regulating monocyte inflammatory responses to gram-negative infections in addition to regulating neuron response in the brainstem for preterm infants.